Potentiation of in vitro apoptotic effects of δ-Tocotrienol and Jerantinine A on human lung adenocarcinoma cells - Ibrahim Babangida Abubakar; Hwei-San Loh (Shahrekord University of Medical Sciences, 2019)
Introduction: The apoptotic effects of single-compound and combined sub-effective concentrations of δ-tocotrienol and jerantinine A on human lung adenocarcinoma (A549) cells were investigated. Methods: Assays including cell viability, histochemical and immunofluorescence staining techniques, flow cytometry and enzyme activity were used. Results: The combination of δ-tocotrienol with jerantinine A at sub-effective concentrations induced a synergistic effect and improved selective toxicity towards cancerous A549 cells over normal lung fibroblast (MRC5) cells compared to the single-compound jerantinine. Morphological features of apoptosis were evident on treated A549 cells. Combined sub-effective concentrations of δ-tocotrienol with jerantinine A induced a predominantly G2/M cell cycle arrest and characterised by a disruption of microtubular networks mediated via caspase 8, 9 and 3 enzymatic activities. Conclusion: These findings demonstrated improved potency in vitro and reduced dose-related toxicity of jerantinine A to normal cells through prospective combined treatment between low-concentration δ-tocotrienol and jerantinine A for lung cancer.